Effect of α-particle irradiation on a NdFeAs(O, F) thin film. (5th February 2018) - Tarantini, C; Iida, K; Sumiya, N; Chihara, M; Hatano, T; Ikuta, H; Singh, R K; Newman, N; Larbalestier, D C
Abstract: The effect of α -particle irradiation on a NdFeAs(O, F) thin film has been investigated to determine how the introduction of defects affects basic superconducting properties, including the critical temperature T c and the upper critical field H c2, and properties more of interest for applications, like the critical current density J c and the related pinning landscape. The irradiation-induced suppression of the film T c is significantly smaller than on a similarly damaged single crystal. Moreover H c2 behaves differently, depending on the field orientation: for H // c the H c2 slope monotonically increases with increasing disorder, whereas for H // ab it remains constant at low dose and it increases only when the sample is highly disordered. This suggests that a much higher damage level is necessary to drive the NdFeAs(O, F) thin film into the dirty limit. Despite the increase in the low temperature H c2, the effects on the J c ( H // c ) performances are moderate in the measured temperature and field ranges, with a shifting of the pinning force maximum from 4.5 to 6 T after an irradiation of 2 × 10 15 cm −2 . On the contrary, J c ( H // ab ) is always suppressed. The analysis demonstrates that irradiation does introduce point defects (PD) acting as pinning centres proportionally to the irradiation fluence but also suppresses the effectiveness of c -axis correlated pinning present in the pristine sample. We estimate that significant performance improvements may be possible at high field or at temperatures below 10 K. The suppression of the J c ( H // ab ) performance is not related to a decrease of the J c anisotropy as found in other superconductors. Instead it is due to the presence of PD that decrease the efficiency of the ab -plane intrinsic pinning typical of materials with a layered structure.